Diagnosis and Management of Alopecia Areata: A Saudi Expert Consensus Statement (2023) - Mohammad Ibrahim Ahmad Fatani; Abdullah Alkhalifah; Amaal Farhan Salman Alruwaili; Aymen Hamed Salem Alharbi; Ru'aa Alharithy; Amr Mohammad Khardaly; Hajer Yousef Almudaiheem; Ahmed Al-Jedai; Maysa Tariq Yousef Eshmawi (Adis, Springer Healthcare, 2023)
Abstract Alopecia areata (AA) is a complex autoimmune disease manifesting as a chronic inflammatory disease characterized by non-scarring patches of hair loss over the face, scalp, and body. Several treatments have been proposed for AA, but none are curative nor achieve a state of remission. The present consensus statement aims to present the evidence- and experience-based recommendations on the diagnosis and management of AA in Saudi Arabia. The Ministry of Health in Saudi Arabia has opted to initiate a meeting of a multidisciplinary group to discuss and concede on this topic. Eight dermatology experts and clinical pharmacists convened in eight consensus meetings. All content presented in this document was agreed upon by this working group, including diagnosis and severity assessment, prognostic indicators, and therapeutic options for AA. Special consideration was given to special patient populations including pediatric patients and patients with less frequent presentations of AA. Updates of the current recommendations will take place as new evidence evolves in the treatment of AA.